Poly (ADP) ribose polymerase enzyme inhibitor, veliparib, potentiates chemotherapy and radiation in vitro and in vivo in small cell lung cancer. (13th August 2014) - Owonikoko, Taofeek K.; Zhang, Guojing; Deng, Xingming; Rossi, Michael R.; Switchenko, Jeffrey M.; Doho, Gregory H.; Chen, Zhengjia; Kim, Sungjin; Strychor, Sandy; Christner, Susan M.; Beumer, Jan; Li, Chunyang; et al.
Abstract Poly (ADP) ribose polymerase (PARP) plays a key role in DNA repair and is highly expressed in small cell lung cancer (SCLC). We investigated the therapeutic impact of PARP inhibition in SCLC. In vitro cytotoxicity of veliparib, cisplatin, carboplatin, and etoposide singly and combined was determined by MTS in 9 SCLC cell lines (H69, H128, H146, H526, H187, H209, DMS53, DMS153, and DMS114). Subcutaneous xenografts in athymic nu/nu mice of H146 and H128 cells with relatively high and low platinum sensitivity, respectively, were employed for in vivo testing. Mechanisms of differential sensitivity of SCLC cell lines to PARP inhibition were investigated by comparing protein and gene expression profiles of the platinum sensitive and the less sensitive cell lines. Veliparib showed limited single‐agent cytotoxicity but selectively potentiated (≥50% reduction in IC50) cisplatin, carboplatin, and etoposide in vitro in five of nine SCLC cell lines. Veliparib with cisplatin or etoposide or with both cisplatin and etoposide showed greater delay in tumor growth than chemotherapy alone in H146 but not H128 xenografts. The potentiating effect of veliparib was associated with in vitro cell line sensitivity to cisplatin (CC = 0.672; P = 0.048) and DNA‐PKcs protein modulation. Gene expression profiling identified differential expression of a 5‐gene panel (GLS, UBEC2, HACL1, MSI2, and LOC100129585) in cell lines with relatively greater sensitivity to platinum and veliparib combination. Veliparib potentiates standard cytotoxic agents against SCLC in a cell‐specific manner. This potentiation correlates with platinum sensitivity, DNA‐PKcs expression and a 5‐gene expression profile.